Bryological herbarium of the Institute of Ecology of the Carpathians of NAS of Ukraine - Лобачевська, О. В.; Рабик, І. В. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology»)
Information about bryological herbarium collections of the Institute of Ecology of the Carpathians (over 20 000 samples) has been provided. The main scientists and areas of collection of samples for bryological research have been represented. Unique findings of bryophytes from Ukrainian and foreign scientists-bryologists, which are stored in herbarium collections, have been listed. Besides materials of systematic herbarium collections, the data about kariological herbarium and its importance for kariosystematics of mosses have been provided. The scientific and historical significance of the herbarium funds that confirm directions, magnitude and intensity of bryological research and promode international cooperation has been noted.